Advanced Support Technologies in Roadway - Liu, Guoming; Hu, Xiangming (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is very useful for scholars studying roadway support. It collects and displays breakthroughs and high-level research progress of advanced support technology, including advanced cement-based materials for tunnel support, advanced surrounding rock control technology, road dust control methods, advanced tunnel support equipment, advanced road disaster control theory, etc. Additionally, this book provides innovative research ideas and reference research methods for scholars who study roadway support. By reading this book, the reader's theoretical knowledge of roadway support, as well as innovative and divergent thinking, will be improved.